(untitled) (Jurnal Pembangunan Sosial, 2017)
Social work as a profession may have been well established in many countries; nevertheless internationally its professional status and professionalization process differs from country to country. Social work in Malaysia has come to a new chapter when the government endorsed a proposal to enact a Social Workers Bill as part of its commitment to enhance the quality of social workers and social work practice in the country. One significant aspect of the draft bill is the registration and licensing of social workers. Drawing examples from a few countries that have registration requirement, this paper attempts to highlight some issues and challenges that may arise when the registration and licensing begin after the bill has been enacted. The legislation can provide a legal framework to put in place proper structures for social work education and development. It however requires all stakeholders to work closely to ensure that eventually the vulnerable populations that the profession is serving can also benefit from the professionalization process.